DEVELOPMENT OF THE TWO-WHEEL TRACTOR COMPOUND TO ENHANCE THE EFFICIENCY OF AGRICULTURAL TASKS IN SMALLHOLDING - Abdel Hussein , Zahraa Abbas; Dawood , Shaima Sami (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
A field experiment was conducted at the Al-Raed Research Station, located 25 km west of Baghdad, to investigate the effects of machine speed and plowing depth on various performance indicators of a mechanized unit. A combined implement was utilized to simultaneously perform multiple agricultural operations. The experiment employed two main factors: forward speed of the mechanized unit, with three levels (1.004, 2.03, and 3.048 km h-1), and plowing depth, with three levels (5, 8, and 10 cm). The performance indicators studied included slip percentage, operating costs (IQD ha-1), the number of soil clods larger than 22 mm in diameter, and Emergence percentage. Through the results obtained in the experiment The initial operational speed of 1.004 km h-1outperformed other treatments in terms of minimal slip (5.48%), reduced soil clod size (17.00 clods/m² > 22 mm), and higher maximum Emergence (85.30%). Nevertheless, it incurred the highest operational cost of 17807 dinars ha1-. Conversely, a plowing depth of 5 cm resulted in the lowest slip (7.42%), cost (15408 dinars ha1-), and soil clod count (18.30 clods/m²), while maintaining a high Emergence rate (84.90%). nested design with a completely randomized block design (RCBD) was adopted.